The specialty of allergy and clinical immunology in Brazil - de Mello, Luane Marques; Serpa, Faradiba Sarquis; Chiabai, Joseane; Fernandes, Fátima Rodrigues; Chong-Neto, Herberto José; Sarinho, Emanuel Sávio Cavalcanti; Rubini, Norma de Paula Motta; Solé, Dirceu (Frontiers in Allergy, 2022)
Objective To assess the profile of allergist/immunologist (A/I) physicians in Brazil, the workplace, the access to diagnostic and therapeutic procedures, and the impact of the COVID-19 pandemic on professional practice. Methods This cross-sectional study was conducted as an online survey. All adhering members of the Brazilian Association of Allergy and Immunology (ASBAI) received a Google Forms tool by email. The questionnaire addressed sociodemographic and professional aspects of the Brazilian allergists/immunologists (A/I) daily routine. The information was analyzed by SPSS version 20.0. Results Four hundred and sixty members answered the questionnaire. Women were predominant among the responders (336; 73%), and the median age was 47 years (range, 27–82 years). Most participants worked in the private sector (437, 95%), whereas 256 (47%) worked in the public sector. Among the public sector employees, 210 (82%) reported having access to some diagnostic test for allergic diseases and inborn errors of immunity. Only 91 (35%) A/I physicians in the public system had access to allergen-specific immunotherapy, compared to 416 (95, 9%) of those in the private sector. Regarding biological drugs, 135 (52.7%) and 314 (71.9%) of the A/I physicians working in the public and private sector, respectively, reported access. Two hundred and eighty-three (61.6%) had at least a 50% reduction in the number of consultations, and 245 (56%) provided telemedicine care during the COVID-19 pandemic. Conclusion Brazilian A/I have incorporated the most recent advances in managing immunoallergic diseases into their clinical practice, but they still have little access to various diagnostic methods. Strategies to enable the presence of A/I in public health services should be discussed and implemented. The coronavirus pandemic has accelerated the incorporation of telemedicine as a viable and promising method of medical care and can expand access to the specialty.